O efeito das extensões de marca sobre a imagem da marca - Serrão, Priscila Norcia (2005)
The objective of this study is to analyze the effect that a brand extension strategy has on the brand image. The present study is analyzed on the Brazilian context, with a sample of 192 consumers and with two different product categories. It is an extension on the article of Martinez e Chernatony (2004). Through a linear regression analysis, it is identified a brand image¿s dilution effect after the extension. The characteristics of the perceived quality, the attitude and the familiarity had a positive effect over the brand after the extension; the similarity had a positive effect only at the brand¿s image. In a complementary way to the original paper, the effects of the interest for the original category are also analyzed and result in a dilution effect after the extension.